Atypical presentations associated with non‐polyalanine repeat PHOX2B mutations. Issue 7 (28th April 2018) - Katwa, Umakanth; D'Gama, Alissa M.; Qualls, Anita E.; Donovan, Lucas M.; Heffernan, Jody; Shi, Jiahai; Agrawal, Pankaj B.
Abstract : Congenital central hypoventilation syndrome (CCHS) is a disorder of ventilatory control and autonomic dysregulation that can be caused by mutations in the paired‐like homeobox 2B ( PHOX2B) gene. The majority of CCHS cases are caused by polyalanine repeat mutations (PARMs) in PHOX2B ; however, in rare cases, non‐polyalanine repeat mutations (NPARMs) have been identified. Here, we report two patients with NPARMs in PHOX2B . Patient 1 has a mild CCHS phenotype seen only on polysomnogram, which was performed for desaturations and stridor following a bronchiolitis episode, and characterized by night‐time hypoventilation and a history of ganglioneuroblastoma. She carried a novel de novo missense variant, p.R102S (c.304C > A), in exon 2. Patient 2 has an atypical CCHS phenotype including micrognathia, gastroesophageal reflux, stridor, hypopnea, and intermittent desaturations. Sleep study demonstrated that Patient 2 had daytime and night‐time hypercarbia with obstructive sleep apnea, requiring tracheostomy. On PHOX2B sequencing, she carried a recently identified nonsense variant, p.Y78* (c.234C > G), in exon 1. In summary, we present two patients with CCHS and identified NPARMs in PHOX2B who have distinct differences in phenotype severity, further elucidating the range of clinical outcomes in CCHS and illustrating the necessity of considering PHOX2B mutations when encountering atypical CCHS presentations.